2020
DOI: 10.1089/hum.2019.352
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Oncolytic Adenovirus Driven by a Chimeric Promoter and Armed with Decorin Against Renal Cell Carcinoma

Abstract: Virus-targeted therapy for tumors can effectively prolong the survival rate of patients and has become a new trend for cancer biotherapy. Oncolytic adenovirus (OAd) can specifically replicate in tumor cells, allowing the therapeutic genes carried to be rapidly copied. As known, solid tumors are always hypoxic, and researchers often overlook a key point, the replication of OAd depends not only on its own activity but also on the cellular hypoxic environment in which the virus replicates. In this study, we const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…A previous study demonstrated that oncolytic viruses controlled under certain promoters could selectively target and kill tumor cells, spreading within the tumor while sparing normal tissue [ 12 ]. We found that our recombinant oncolytic adenovirus did not infect normal brain cells, such as HMC3 and BV2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that oncolytic viruses controlled under certain promoters could selectively target and kill tumor cells, spreading within the tumor while sparing normal tissue [ 12 ]. We found that our recombinant oncolytic adenovirus did not infect normal brain cells, such as HMC3 and BV2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Adenoviral E1A is necessary and plays an important role in the process of viral infection and replication [ 12 ]. The Ki67 promoter regulates transcription of the E1A gene, and IL-15 was inserted into the viral genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An engineered oncolytic adenovirus expressing decorin named OAV-Decorin (OAV-DEC) was constructed previously, 33 in the backbone of a tumor-selective oncolytic adenovirus ZD55 vector, in which E1B-55KD had been deleted. HEK293 cells were used to amplify virus OAV-DEC or control vector virus OAV with a density of about 80%, when half of the cells were floated, the viruses were collected and the titers were measured by tissue culture infection dose 50 (TCID50) methods.…”
Section: Methodsmentioning
confidence: 99%
“…During infections, viruses hijack host cells replication mechanisms, promote their own genetic expression, and unavoidably cause the death of host cells, allowing viral offspring to reach and infect neighboring host cells ( Martinez-Velez et al, 2019 ). OVs can specifically infect and kill tumor cells and have become an attractive treatment choice ( Fang et al, 2014 ; Martikainen and Essand, 2019 ; Zhang W. et al, 2020 ). Our research team has showed that OVs have potent therapeutic efficacy and safety to treat malignant brain glioma and uveal melanoma ( Zhang J. et al, 2020 ; Liu et al, 2020a ; Zhang Q. et al, 2020 ; Liu et al, 2020b ; Liu et al, 2021 ).…”
Section: Potential Clinical Applicationsmentioning
confidence: 99%